TOPONIMI DI WILAYAH PASAMAN DAN TANAH DATAR SUMATERA BARAT BERDASARKAN NASKAH TAMBO TUANKU IMAM BONJOL ABAD 19 MASEHI - Lestari, Dinda; Sunliensyar, Hafiful Hadi; Wardoyo Adi, Ari Mukti (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2025)
This study aims to examine the toponyms located in Pasaman and Tanah Datar Regencies based on the Tambo Tuanku Imam Bonjol Manuscript. This manuscript is an authentic historical record of important events in Minangkabau, particularly during the Padri War. The focus of this study is to identify toponyms in Pasaman and Tanah Datar Regencies based on their geographical location and their connection to archaeological remains. The method used in this study is a qualitative method with a descriptive-analytical approach, which includes data collection, data processing (analysis), interpretation, and drawing conclusions from the issues. The theory used refers to Agus Aris Munandar's theory, which is divided into three aspects: 1) The meaning of the place name, 2) The current existence of the location, 3) The role of contemporary culture. The results of the study indicate that there are 43 toponyms in Pasaman Regency and 11 toponyms in Tanah Datar Regency. Out of the 54 toponyms, only 9 were selected as the focus of the study. These toponyms are still in use today and are associated with the figure of Tuanku Imam Bonjol and the Padri War. This is also supported by contemporary archaeological remains in the areas mentioned in the manuscripts.